1997
DOI: 10.1002/(sici)1097-4598(199706)20:6<679::aid-mus4>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in motor unit function

Abstract: This review focuses on the functional relationship between age‐related morphological and physiological changes at the level of the motor unit (MU). It is well established that older humans are weaker than younger people, exhibit reduced force control, and have slower neuromuscular contractile properties. Older people may also exhibit a decrease in MU discharge rate, and an increase in variability of MU discharge at high force levels. The matching of MU discharge and contractile properties may be an age‐related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 292 publications
(107 citation statements)
references
References 114 publications
4
101
1
Order By: Relevance
“…Factors associated with muscle fatigue include aging, disease, gender, nutrition, physical activity, subjective fatigue, inflammation, muscle strength, size, structure, metabolism, and blood flow, and neural and hormonal factors (Abbiss and Laursen 2005;Allman and Rice 2001;Hunter et al 2004;Roos et al 1997;Vandervoort 2002;Vandervoort and Symons 2001). To our knowledge, no one has examined the association between frailty and muscle fatigue.…”
Section: Frailty and Muscle Fatiguementioning
confidence: 99%
See 4 more Smart Citations
“…Factors associated with muscle fatigue include aging, disease, gender, nutrition, physical activity, subjective fatigue, inflammation, muscle strength, size, structure, metabolism, and blood flow, and neural and hormonal factors (Abbiss and Laursen 2005;Allman and Rice 2001;Hunter et al 2004;Roos et al 1997;Vandervoort 2002;Vandervoort and Symons 2001). To our knowledge, no one has examined the association between frailty and muscle fatigue.…”
Section: Frailty and Muscle Fatiguementioning
confidence: 99%
“…Investigators have examined the differences in fatigability between various muscles in young and older adults (Allman and Rice 2001;Roos et al 1997), yet findings vary among studies (Chan et al 2000). Some studies have shown that older adults experienced less fatigue than younger adults during isometric, isokinetic, and isotonic contractions (Hakkinen 1995;Hunter et al 2004Hunter et al , 2005Yassierli and Nussbaum 2007), whereas other researchers reported that older adults exhibit greater fatigue during isotonic and electrical stimulation contractions (Cupido et al 1992;McNeil and Rice 2007;Petrella et al 2005), and still others report the existence of no age-related differences during isometric, isokinetic, and electrical stimulation contractions (Klein et al 1988;Lanza et al 2005;Smolander et al 1998; (Table 2).…”
Section: Agingmentioning
confidence: 99%
See 3 more Smart Citations